2007
DOI: 10.1080/10407780600939628
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Conjugate Heat Transfer During Free Liquid Jet Impingement on a Rotating Disk

Abstract: The aim of this computational study is to characterize convective heat transfer for a free liquid jet impinging on a rotating and uniformly heated solid disk of finite thickness and radius. Calculations are done for a number of disk materials and working fluids covering a range of Reynolds number (445-1,800), Ekman number (2.21 3 10 À5 -2.65 3 10 À4 ), nozzleto-target spacing (b ¼ 0.55-5.0), disk thicknesses-to-nozzle diameter ratio (0.167-1.67), disk-to-nozzle diameter ratio (2.11-6.33), Prandtl number (1.29-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Rahman et al 12,13) numerically characterized the convective heat transfer of a free liquid jet impinging on a rotating, uniformly heated solid disk with finite thickness and radius. Chen et al 14) studied the heat transfer between a circular impinging jet and a moving metal plate at temperatures above and below the boiling point of water by means of experiments and numerical simulations.…”
Section: Literature Surveymentioning
confidence: 99%
“…Rahman et al 12,13) numerically characterized the convective heat transfer of a free liquid jet impinging on a rotating, uniformly heated solid disk with finite thickness and radius. Chen et al 14) studied the heat transfer between a circular impinging jet and a moving metal plate at temperatures above and below the boiling point of water by means of experiments and numerical simulations.…”
Section: Literature Surveymentioning
confidence: 99%
“…(22) will be equal to zero at the final iteration step. Computational experience has shown that it is advisable to use the discrepancy principle [19] for terminating the iteration process in the conjugate gradient method, i.e., it is assumed that the residuals for the temperatures may be approximated by T s (x m , y m ) À Y(x m , y m ) ffi r, where r is the standard deviation of the temperature measurements, which is assumed to be a constant. Substituting the approximation T s (x m , y m ) À Y(x m , y m ) ffi r into Eq.…”
Section: Stopping Criteriamentioning
confidence: 99%
“…Therefore, the direct problem is a forcedconvection heat transfer problem, and the steady two-dimensional governing equations and boundary conditions can be written as [19]: Navier-Stokes equations:…”
Section: Direct Problemmentioning
confidence: 99%
“…Computations were performed using a two-dimensional axisymmetric Eulerian mesh while the free surface was calculated with the volume of fluid method. Rahman and Lallave [21] numerically studied the convective heat transfer performance of a free liquid jet impinging on a rotating and uniformly heated plane solid disk of finite thickness and radius. A generalized average Nusselt number correlation was developed from numerical results.…”
Section: Introductionmentioning
confidence: 99%